EFFECTS OF A TRAINING PROGRAM FOR THE PLYOMETRIC ON THE HARMONIC ABILITIES AND MUSCULAR ABILITY OF FOOTBALL PLAYERS - Hasan Jasim Hussein Al Behadili; Munadhil Adil Kasim (Journal Park Publishing, 2022)
Plyometric training (PT) is a method for enhancing harmonic abilities and muscular. It consists of physical workouts in which muscles exert maximal force for brief times in order to improve harmonic abilities performance. Among the most essential qualities that football play concentrates on are perhaps physical ability and harmonic ability on the one hand, and the skills of shooting precision towards the foot and bending, which are among the foundations of play and the criteria for winning competitions. In an effort to develop these features and find out how they relate to various elements of muscular ability, we proposed to try a training program focused on the method of plyometric training. Which is one of the techniques intended to promote muscular growth that is direct and, in turn, has an impact on the leve of harmonic skills. The under-18 age group was chosen for the study sample due to the characteristics of this group in terms of the stages of physical, physiological, psychological, and mental development, we used a variety of tests in our research to assess both harmonic and muscular abilities, the results were also analysed and interpreted using a set of statistical laws and methods, and they were compared to the study's assumptions. One of the most significant conclusions we came to was that the results, the presence of statistically significant differences between the pre- and post-tests in the tests of explosive strength of the lower limbs, the upper limbs, and the strength tests that reflect speed in the sport of football, additionally, there were statistically significant differences between the pre- and post-tests in favour of the dimensional orienting ability tests that were administered as well as assessments of adaptability to changing situations in the football field.
Keywords: Training Program, Plyometric, Harmonic Abilities, Muscular Ability.